IMPLEMENTASI KETRAMPILAN UMKM STRATEGI MEMASUKI PASAR DIGITAL - Muchayatin Muchayatin; Dirgo Wahyono; Sukardi Sukardi; Anisa Sukmawati; Sutarno Sutarno (Perigel: Jurnal Penyuluhan Masyarakat Indonesia, 2022)
Today, digital technology is developing rapidly, from its application to the emergence of various digital business entities. The application of the Internet and digital technologies is geared towards achieving marketing goals. The goal of marketing is to win the competition. So a strategy is needed to enter the digital market. Community service. This aims to provide knowledge to Cemara MSMEs regarding strategies to enter the digital market, especially the results of milkfish processing in Kaliprau Village, Ulujami District, Pemalang Regency. This method of community service activities uses the method of lectures, dialogues and questions and answers. The results obtained by participants understand the reach and breadth of the digital market and are able to measure the ability to enter the digital market. The enthusiastic response from the participants received input on the needs of Cemara MSMEs related to skills in using information technology, transaski using e-money applications and bookkeeping.